Effects of volleyball match-induced fatigue on knee joint position sense - Ribeiro, F.; Santos, F.; Goncalves, P.; Oliveira, J. (European Journal of Sport Science, 2008)
It has been suggested that a greater number of injuries during the last third of practice sessions or matches could be related to alteration of lower limb neuromuscular control due to neuromuscular fatigue. This fatigue-related effect can be mediated by changes in joint proprioception. In athletes, the use of functional fatigue protocols could have the advantage of mimicking the demands of sporting activity, thus reflecting more specifically the changes in neuromuscular control and proprioception observed in sport settings. The purpose of the present study was to assess the effect of fatigue induced by a volleyball match on knee joint position sense in elite volleyball players. Seventeen female volleyball players aged 18.9±4.2 years from the Portuguese national team volunteered for the study. Knee joint position sense was evaluated by an open kinetic chain technique and active knee positioning, and was reported using absolute, relative, and variable angular errors. Joint position sense measures were obtained before and immediately after a simulated volleyball match of five sets. To ensure that the match was sufficiently intense to induce fatigue, the perceived exertion or exercise intensity was assessed at the end of the match using Borg' s rating of perceived exertion (RPE) scale. All participants completed the volleyball match (90min duration), reaching or exceeding 15 on the RPE scale (15.59±0.71; range 15-17), equivalent to "hard/heavy work". After the volleyball match, a significant increase in absolute (2.11°) and relative (1.71°) angular errors was detected. Match-induced fatigue significantly exacerbated the overestimation of the test position. Moreover, the reliability and accuracy in estimating knee angles decreased from rest to the fatigued state, as shown by the increase (264%) in variable error. Our results show that fatigue induced by a volleyball match has a marked effect on knee joint position sense in elite female volleyball players. Knee joint position sense was less accurate and less consistent after the volleyball match. Fatigue induced by a simulated competitive volleyball match resulted in proprioceptive deficits, decreasing sensorimotor system acuity in female volleyball players.